Mechanism and ligand design in ruthenium catalysis - Jabri, Amir (University of Ottawa (Canada), 2005)
The known ruthenium pincer complex RuCl(eta3-dcpx)(PPh 3) (7) (PCP = eta3-2,6-(PCy2CH 2)2C6H3) was transformed into several different hydride products under standard transfer hydrogenation conditions. In situ 31P NMR analysis during thermolysis of 7 in basic isopropanol permitted identification of RuH(eta3-dcpx)(PPh 3)(N2) (8a/b), RuH(eta3-dcpx)(PPh 3) (10), and RuH(eta3-dcpx)(PPh3 )(H2) (9a/b). A spectroscopically unobservable species, Ru(H)2[eta2-PC(H)P] (12), is proposed as the active species in transfer hydrogenation catalysis. The novel precatalyst, RuCl(eta3-dcpx)(py)2 ( 14), which may provide a more active catalyst, was synthesized and characterized. Several primary and secondary phosphine complexes of ruthenium were synthesized and tested for their activity in catalytic transfer hydrogenation. Of these, only the bulky HPCy2 ligand in RuCl2(HPCy2) 4 (18a/b) provided high catalytic activity. Reaction of RuCl2(PCy3)2(=CHPh) (24) with HPCy2 transforms it cleanly to 18a, potentially opening new opportunities in tandem catalysis. (Abstract shortened by UMI.)
Keywords: Chemistry, Organic.